Impact of Macroeconomic Variables on The Share Price of Mining Company Noted In The Islamic Jaccarta Index - Three Handayani Nabila Pratiwi; Ahmad Syakir; Aqwa Naser Daulay (Dinasti Publisher, 2024)
The aim of this study is to assess the impact of GDP, currency exchange rates, and inflation rates, both separately and jointly, on the stock price of the mining companies included in the Jakarta Islamic Index in 2017 to 2022. The panel data analysis used in this study is a study approach, and uses E-Views 12. Estimate findings show that the stock price of the companies included in the Jakarta Islamic Index is significantly influenced by the exchange rate. The price of the index's mining business stocks was significantly affected by the rise in the dollar exchange rate. However, under certain circumstances, the rate of inflation studied is within a stable range, that is, below 10% per year, so the inflation rate is relatively ineffective. Although there is progress in real-sector investment, the limited influence of GDP may be due to the slow rise in investment in capital markets. As a result, the influence of GDP variables on the stock price of mining companies is only small.